When foundation matters: overcoming legal and regulatory barriers to oil and gas well decommissioning in Russia. (23rd April 2018) - Sidortsov, Roman; Gavrilina, Elena
Abstract: The Russian Federation has an acute problem of orphan and runaway oil and gas wells. Deficiencies in the decommissioning requirements under Russian law are one of the main causes of the problem. The principal aim of this article is to explore the legal origins of barriers to effective and efficient decommissioning in Russia and propose potential solutions. The article begins with an overview of the current legal and regulatory framework governing permanent and temporary decommissioning in the context of the Russian legal system's particularities. A critique of the contradicting statutory and regulatory provisions and excessively prescriptive requirements is offered. The article continues with exploring the problem that compounds the shortcomings of the decommissioning legal framework—a misalignment of the legal status of a well under property laws and the laws and administrative regulations governing oil and gas well decommissioning. The article concludes with recommendations regarding the initial step to remedy this complex and compounded problem.